ATTITUDES OF FOREIGN LANGUAGE TEACHING STUDENTS TOWARDS ONLINE LEARNING - Üstün, Bilal; Aksu Ataç, Bengü (International Online Journal of Education and Teaching, 2022)
In this study, it is aimed at revealing the attitudes of foreign language teaching students towards online learning. For this purpose, survey model, one of the quantitative research methods, was used. The universe of the research consists of students studying foreign language teaching at universities in Turkey, while the sample consists of students studying German and English teaching at a state university located in the Central Anatolia region of Turkey. A total of 210 participants took part in the study. The data obtained from the participants within the scope of the research were analyzed using the SPSS 21 package program. Evaluation of normally distributed data was done by t-test in paired groups and by one-way analysis of variance (ANOVA) in groups of more than two. As a result of one-way analysis of variance (ANOVA), Tukey’s test, one of the Post-Hoc tests, was used to determine which groups caused the difference for the data with significant difference. As a result, it was concluded that male participants accepted online learning more than female participants, the participants’ attitudes towards online learning did not differ according to their departments and the general acceptance perceptions of online learning of the participants in the third grade were higher than the participants in the second grade.